Structure-dynamics relation in metallic glass revealed by 5-dimensional scanning transmission electron microscopy - Katsuaki Nakazawa; Kazutaka Mitsuishi; Konstantin Iakoubovskii; Shinji Kohara; Koichi Tsuchiya (NPG Asia Materials)
Abstract Dynamical and structural heterogeneities play an important role in glass transition phenomena. However, the relation between these heterogeneities is not fully revealed. In this study, we simultaneously observed these heterogeneities near the glass transition temperature in Zr50Cu40Al10 using five-dimensional scanning transmission electron microscopy, which can record the spatiotemporal distribution of diffraction patterns. The heterogeneities were visualized with sub-nanometer resolution, and a correlation between them was measured up to the glass transition temperature. We verified that ordered structures had slow dynamics, and the order decreased as the temperature increased.